Severe neurological presentation in COVID-19 - Vásquez-Colina, Alfredo (2020)
This is the case of a 53-year-old male with a three-day disease time, with malaise, fever, pharyngeal pain and dry cough. Upon entering the hospital, he was febrile and had tonic- clonic seizures and disorientation. The pulmonary tomography showed COVID-19-compatible lesions; normal brain CT; and, rT-PCR for COVID-19: positive. The lumbar puncture showed only hyperglucorraquia, The patient died on the third day. It is concluded that it was a patient with COVID-19 and neurological involvement type encephalitis.